STUDY OF SOME OF THE TECHNICAL AND ECONOMICAL INDICATORS FOR DIFFERENT MECHANIZATION SYSTEMS IN THE SEMI QUARANTEED RAIN REGION - Saddam Hussen Al lwayzy (Mesopotamia Journal of Agriculture)
This study was conducted in Nineveh, Humaedat region which located in the semi guaranteed rain region, for the 2004-2005 agricultural season, to see some indicators of economic assessment and technological indicators, by taking data from the four companies (different mechanization systems) to plant wheat and barley crops for making comparison among them for tillage, planting and harvesting to find the values of these indicators of the total agricultural operations and the average of these companies and to compare with some universal values. The average values of the four companies in the total agricultural operation, showed that the fuel consumption was 24.8 L/ha, 21.3 L/hr, specific fuel consumption 0.17 L/kw.hr. The percentage of fuel costs from the total costs 7.8% and the percentage of the fuel cost of mechanization costs 17.5%.While one kw serving area of land 0.76 hectares, the share of the tractors and harvesters of the earth 589 ha/tractor, 688 ha/harvester respectively. the Average of the time work of tractors and harvesters per year 529 and 419 hr/year respectively. The average productivity of the season 0.42 ha/hr, actual productivity 0.85 ha/hr. The work efficiency of the agricultural season was 48%, and the human effort 3.07 man.hr/ha. The agricultural worker share of the land 41.72 ha/man. The cost of mechanization to planting one hectare was 14382 ID. The percentage of mechanization cost of total costs 44%. The effectiveness of total capital was 1.48. The effectiveness of mechanization capital was 3.61 where yields were 264.2 kg/ha.